TRAINING ON USE OF USER-FRIENDLY R-SHINY PROGRAM FOR DETERMINING NUTRITIONAL STATUS OF TODDLERS AT POSYANDU IN THE WORKING AREA OF THE SOBO BANYUWANGI COMMUNITY HEALTH CENTER - Chamidah, Nur; Kurniawan, Ardi; Saifudin, Toha; Easyfa Wieldyanisa, Ezha; Insania Dewanty, Sanda; Azizah, Khansa (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Stunting is a form of malnutrition that serves as an important indicator for monitoring the growth and development of toddlers. However, assessing the nutritional status of toddlers does not stop at stunting, but includes a comprehensive understanding of the child's nutritional condition in real time, especially by mothers who have toddlers. Although the prevalence of stunting in Indonesia has decreased, achieving the target reduction to 14% by 2024 still requires significant efforts. This community service activity aims to improve the nutritional literacy and technical skills of posyandu cadres and mothers of infants in utilizing a user-friendly R-Shiny-based application, both in web and Android versions. This application allows users to input anthropometric data of infants (weight-for-age, height-for-age, and BMI-for-age), and then automatically generates growth charts based on reference standards. The activity was conducted in a hybrid format on June 29, 2024, with a total of 69 participants (35 offline cadres and 34 online cadres). Evaluation results showed a significant increase in cadres' knowledge, with an average post-test score (76.81) higher than the pre-test score (71.66) and a p-value from the paired t-test of 0.008. Additionally, participants gave high satisfaction scores, with an average above 75 on all indicators. The program also provides intensive mentoring and long-term monitoring to ensure smooth application use. With a data-driven approach sensitive to regional characteristics, this program is expected to serve as an innovative, sustainable, and replicable community service model in other areas to accelerate stunting reduction efforts.